Facing catastrophe : environmental action for a post-Katrina world - Verchick, Robert R. M. (Harvard University Press, 2010)
"In this bold contribution to environmental law, Robert Verchick argues for a new perspective on disaster law that is based on the principles of environmental protection. His prescription boils down to three simple commands: Go Green, Be Fair, and Keep Safe. Going green means minimizing exposure to hazards by preserving natural buffers and integrating those buffers into artificial systems like levees or seawalls. Being fair means looking after public health, safety, and the environment without increasing personal and social vulnerabilities. Keeping safe means a more cautionary approach when confronting disaster risks"--Publisher.